Planning Problems in the Limited Liability Company - Dennis S. Karjala (Washington University Law Quarterly, 1995)
Part I briefly discusses the development of the limited liability company form and its roots in the liberalized provisions of modem corporation and partnership law. In Part II, the Article examines a variety of fact situations derived from partnership and close corporation case law as examples of the kinds of disputes that arise among the participants in closely held enterprises.
Keywords: Private companies; Close corporations; Corporate governance